An optimized embryonic stem cell model for consistent gene expression and developmental studies - Gissel, Cornelia; Voolstra, Chris; Doss, Michael Xavier; Koehler, Christoph I.; Winkler, Johannes; Hescheler, Jürgen; Sachinidis, Agapios (Thrombosis and Haemostasis, 2005)
In vitro differentiation of embryonic stem (ES) cells results in generation of tissue-specific somatic cells and may represent a powerful tool for general understanding of cellular differentiation and developmentin vivo. Culturing of most ES cell lines requires murine embryonic fibroblasts (MEF), which may influence adventitiously the genetic differentiation program of ES cells. We compared the expression profile of key developmental genes in the MEF-independent CGR8 ES cell line and in the MEFdependent D3 ES cell line. Using neomycin-resistant MEFs we demonstrated that MEFs are able to contaminate the D3 ES cells even after removing the MEFs. Subsequently, optimal differentiation conditions were established for the differentiation of CGR8 ES cells into various germ layer cells. Detailed gene expression studies in differentiating CGR8 cells were done by RTPCR analysis and by microarray analysis demonstrating a general trend of the assessed genes to be expressed either in 3 days- or 10-days old embryoid bodies (EBs) when compared to undifferentiated ES cells. Subsets within the various functional gene classes were defined that are specifically up- or down-regulated in concert. Interestingly, the present results demonstrate that developmental processes toward germ layer formation are irreversible and mostly independent of the culture conditions. Notably, apoptotic and mitochondrial ribosomal genes were downand up-regulated in 10-days old EBs, respectively, whereas compared to the 3-days old EBs whereas the activity of the extracellular signal-regulated kinase (ERK)1/2 decreased with progressive development. This article defines a platform for ES cell differentiation and gene expression studies.Supplementary information available online atwww.uni-koeln.de/med-fak/physiologie/np/sachinidis.htm
Keywords: CGR8 embryonic stem cells; gene expression; microarrays; development